2. Glucose levels of Canis familiaris Urine in Lamposi Tigo Nagori Payakumbuh Using Semiquantitative Striptest - Fhatania Amalia; Roslizawaty Roslizawaty; Rusli Rusli; Arman Sayuti; M Hasan; Amiruddin Amiruddin; Zuraida Zuraida (Universitas Syiah Kuala, 2017)
The aim of this study was to detect the glucose in urine of Canis familiaris as a medical record and a supporting early diagnostic. Urine of thirty local dogs collected from Lamposi Tigo Nagori, Sumatera Barat. Before feeding, urine was collected individually in the morning two times. This study was doing on January 2016. The strip test was soaked in urine (5-10 ml) for 30 second directly. Data of glucose was analyzed using 4 scale discoloration of semi quantitative striptest. The result showed that glucose was not detected on 25 dogs out of 30 of C. familiaris. Amount of 5 C. familiaris were detected the presence of glucose with small (100 mg/dl) scale. We concluded that the levels of glucose C. familiaris urine performed on the tolerance limits of glucose level.